A Rehabilitation Program Accompanied by an (Hp. Laser) Device to Reduce Injury Pain and Increase Range of Motion (S.T.T) for Weightlifting Athletes with Disabilities - Atheer Fawaz Karim (Sinar Sport Journal, 2025)
Inside the bustle of the city, all kinds of sounds fill the air, which interfere with each other like vying musicians. The brilliant neon lights of colossally tall buildings pierce the night sky. This bizarre glow blankets the city below them. A numbing crowd for pedestrian movement. In firecracker like succession, the smell of grilling food on street side mixes with the fumes of gaseous states. This all is a sort of overdosage from aroma saffron that lingers plenty long afterwards. For all this mayhem, there's an unmistakable vitality that flows through the city. It's a relentless heartbeat that pushes things into night. The researcher aims to: (1) Identify the effect of a rehabilitation program accompanied by a laser device on athletes with disabilities suffering from shoulder joint muscle injuries in weightlifting. (2) Identify the effect of the rehabilitation program accompanied by a laser device on increasing the range of motion of the muscles. (3) Identify the effect of the rehabilitation program accompanied by a laser device on reducing. The nature of the phenomenon addressed by the researcher determines the research methodology. Accordingly, the experimental method was adopted due to its suitability for the nature of the research problem and its objectives. The research population was intentionally selected and consisted of weightlifting athletes with disabilities suffering from shoulder joint muscle injuries from the Sub-Paralympic Committee in Al-Diwaniyah. Tests Used in the Research: (1) Shoulder Joint Range of Motion Test during Anterior Elevation (Akram Khattabiya, 1997, p. 67). This test aims to measure the range of motion of the shoulder joint during anterior elevation using a goniometer. (2) Pain Intensity Measurement Using the Visual Analogue Scale (V.A.S.) (2:42). The researcher adopted the Visual Analogue Scale (V.A.S.) to measure pain intensity. This scale is simple and effective for assessing pain severity and is widely used in motor rehabilitation programs. It provides a numerical rating ranging from 0 to 10, starting with “no pain” and ending with “very severe pain.” Conclusions is The prescribed rehabilitation exercises had a significant effect in reducing injury-related pain and increasing the range of motion among weightlifting athletes with disabilities.